Pengaruh Model Pembelajaran REACT Untuk Meningkatkan Kemampuan Berpikir Kritis di Kelas VII Materi Zat Dan Perubahannya - Latifa Dewi, Shofia; Indah Suryani, Dwi; Aprelia Resti, Vica Dian (PendIPA Journal of Science Education, 2026)
This study was conducted to assess the contribution of the REACT model in enhancing students’ critical thinking skills in learning about substances and their changes at a public junior high school in Serang City. A quantitative approach was employed, using a pretest–posttest control group design, where Class VII C served as the experimental group applying the REACT model, while Class VII A functioned as the control group using the PBL model. Data were collected through multiple instruments, including interviews, questionnaires, test documentation, and observations, and were subsequently analyzed using homogeneity and normality tests, followed by an independent sample t-test. The results indicated an increase in the experimental group’s posttest mean score to 78, outperforming the control group’s mean score of 66, with a significance value of 0.003, below the 0.05 threshold. These findings confirm that the implementation of the REACT model effectively enhances students’ critical thinking skills through the stages of Relating, Experiencing, Applying, Cooperating, and Transferring. Therefore, the REACT model can be considered a viable alternative science teaching strategy that supports the development of students’ critical thinking abilities.